2020
DOI: 10.9734/cjast/2020/v39i2630902
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany, Phytochemical, Pharmacological Potentials of Murraya koenigii, and Its Health Benefits – A Review

Abstract: Murraya koenigii, also widely known as curry leaves and curry patta, is a noticeably significant plant recognized all around the world for its tremendous therapeutic, medicinal worth and characteristic aromatic properties. It is one of the major export commodities originated from east and southern part of India bringing good foreign revenue. This review article is designed to assess and compile all the currently available literature on ethnobotanical aspects and phytochemical, pharmacological potentials of M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Minor chemical constituents such as moisture (63.2 %), fat (6.15 %), total sugars (18.92 %), starch (14.6 %), crude fiber (6.8 %), acid insoluble ash (1.35 %), total nitrogen (1.15 %), phosphorus, thiamine, iron, riboflavin, vitamin C, carotene, oxalic acid, and niacin. [7,10,[19][20] Mahanimbine, isomahanine, koenimbine, mahanine, and girinimbine were isolated from the seeds of M. koenigii (L.) Spreng. Experimental work revealed that the petroleum ether seed extract contained 2-methoxy-3-methylcarbazole.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minor chemical constituents such as moisture (63.2 %), fat (6.15 %), total sugars (18.92 %), starch (14.6 %), crude fiber (6.8 %), acid insoluble ash (1.35 %), total nitrogen (1.15 %), phosphorus, thiamine, iron, riboflavin, vitamin C, carotene, oxalic acid, and niacin. [7,10,[19][20] Mahanimbine, isomahanine, koenimbine, mahanine, and girinimbine were isolated from the seeds of M. koenigii (L.) Spreng. Experimental work revealed that the petroleum ether seed extract contained 2-methoxy-3-methylcarbazole.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Each fruit contains one seed 11 mm long and 8 mm in diameter. They are edible and contain 0.76 % volatile oil [10–12] …”
Section: Morphological Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ethno-medicine, it is used as an anti-dysentric, anti-diabetic and stimulant (14). In Indian this plant is extremely valued for its leaves as an important ingredient to promote digestion and appetite.…”
Section: Ethnobotanical Use Of Murraya Koenigiimentioning
confidence: 99%
“…[1] MK plant is used for its antioxidative, antimicrobial, cytotoxic, antiulcer, positive inotropic, and cholesterol reducing activities. [2] Several compounds have been isolated from different parts. Mathur et al(2011) confirmed the antifungal activity of some components of M. koenigii.…”
mentioning
confidence: 99%